Behavioral decision-making of the government, farmer-specialized cooperatives, and farmers regarding the quality and safety of agricultural products - Yun Teng; Yun Teng; Boyuan Pang; Jingbo Wei; Li Ma; Huihui Yang; Zhanwei Tian (Frontiers Media S.A., 2022)
The quality and safety of agricultural products is very important for farmers' professional cooperatives. This study incorporates the government, farmers' professional cooperatives and farmers into the evolutionary game model to explore the game relationship and evolutionary path of decision-making among the three parties related to the quality and safety of agricultural products. Through the dynamic analysis of decision-making replication, the analysis of strategy evolution stability and the verification of numerical simulation experiments, it is shown that the decision-making behavior of the government, farmers' professional cooperatives and farmers under the conditions of agricultural product quality and safety is the result of the game between three stakeholders; the government, farmers' professional cooperatives and farmers The evolution process of the decision-making behavior to the ideal state is affected by many factors, and the value ranges of different factors have different effects on the convergence speed of the three stakeholders to the ideal state; when certain conditions are met, the government, farmers' professional cooperatives and farmers' three The decision-making behavior of each stakeholder can evolve into an ideal state, and effective government supervision can promote the cooperatives to manage the green production of farmers, and then effectively encourage farmers to take the initiative in green production. In order to provide useful suggestions for the government to make safety supervision decisions, to effectively manage cooperatives, and to stimulate active green production behaviors by farmers.